The Concept of Intellectual Development from the Epistemological Perspective of Islamic Education - Afryansyah, Afryansyah; Ismail, Farji; Ismail, Ismail; Zuhdiyah, Zuhdiyah; Nurbuana, Nurbuana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic education today is facing serious epistemological challenges amidst the dominance of globalization, secular knowledge paradigms, and technological advancement. This study aims to explore the concept of intellectual development within the epistemological framework of Islamic education, particularly through the integration of bayani (textual), irfani (spiritual-intuitive), and burhani (rational-empirical) approaches. This research employed a qualitative method using a library research model with descriptive-analytic analysis. Data were collected from books, academic journals, and scholarly reports, and analyzed using content and thematic analysis. The findings reveal that each epistemological model has unique contributions: bayani strengthens textual authority, irfani develops moral-spiritual depth, and burhani fosters critical and logical reasoning. When integrated, these models offer a holistic approach to intellectual development in Islamic education that balances cognitive, ethical, and spiritual dimensions. The study concludes that to address current educational crises—such as moral degradation and critical thinking decline—Islamic education must embrace an integrative epistemology to form learners who are intellectually sharp, spiritually rooted, and morally guided.